The e-learning-based group investigation (gi) effectiveness on student biology learning outcomes - Azrai, Eka Putri; Razak, Ayyi Ayra; Sartono, Nurmasari (Biosfer: Jurnal Pendidikan Biologi, 2023)
Learning outcomes are one of the parameters of achieving learning objectives. The Covid-19 pandemic condition causes learning to take place remotely so that the delivery of material cooperatively and interactively is hampered. Learning that is not interactive can affect student learning outcomes so appropriate learning models and media are needed. This study aims to determine the effect of using the e-learning-based cooperative learning model type GI (Group Investigation) on student learning outcomes on the material of the circulatory system. This research was conducted in the odd semester of the 2021/2022 academic year at SMA Negeri 44 Jakarta, Indonesia. This type of research is quantitative with a quasi-experimental method and a pretest-posttest non-equivalent control group design. The sample in this study amounted to 67 students with 34 students in the experimental class and 33 students in the control class. The data analysis technique used was the Mann-Whitney test with a significant level (